Candle Soot derived Fractal-like Carbon Nanoparticles Network as High-Rate Lithium Ion Battery Anode Material. (20th October 2015) - Kakunuri, Manohar; Sharma, Chandra S.
Abstract: In this article, we report a facile and inexpensive approach to synthesize fractal-like interconnected network of carbon nanoparticles from candle soot and its direct application as anode material for high-rate lithium ion batteries used for electric vehicles. At low charge/discharge rate (0.5C), an initial discharge capacity was found to be 1997 mAh/g with moderate 30% coulombic efficiency that increased to 91% after 10 cycles. More importantly, at very high charge/discharge rate (10C), reversible capacity was stabilized at 170 mAh/g even after 1000 cycles. This remarkable electrochemical performance may be ascribed to unique morphology of these hard carbon nanoparticles that reduces the diffusion length and also allows fast adsorption/desorption of Li ions on their surface.